Neuromyelitis Optica in a Nepalese Man - Yogesh Subedi; Utsav Joshi; Sanjeeb Sudarshan Bhandari; Ashbina Pokharel; Ashbita Pokharel (Case Reports in Neurological Medicine)
Background. Neuromyelitis optica is a severely disabling inflammatory disorder of the central nervous system of autoimmune etiology that mainly affects the optic nerves and spinal cord. Here, we present a case report detailing a patient with tingling and weakness of right upper and lower limbs who was neuromyelitis optica immunoglobulin G-positive. Case Presentation. A 46-year-old Nepalese man presented to the hospital with a history of tingling and weakness of right upper and lower limbs that developed over a period of two months. Clinical evaluation showed diminished power across all major muscle groups in the right upper and lower limbs. Magnetic resonance imaging of his cervical spine showed T1 iso- to hypointense signal and T2 hyperintense signal in central cervical spinal cord from first to sixth cervical level, probably suggestive of myelitis or demyelination. The patient was immediately started on intravenous methylprednisolone. The diagnosis of neuromyelitis optica was later confirmed with strongly positive neuromyelitis optica immunoglobulin G. Conclusion. In resource limited setting, in the absence of tests for neuromyelitis optica immunoglobulin G, treatment was started and the patient’s condition started to get better. Hence, early initiation of aggressive immunosuppressive treatment is essential in such cases.